Modularity, Linearization and Phase-Phase Faithfulness in Kayardild - Surkalovic, Dragana (IBERIA: An International Journal of Theoretical Linguistics, 2011)
This paper investigates the effects of the Multiple Spell-Out Hypothesis (MSOH) (Uriagereka 1999, Chomsky 2000, 2001, 2004) on the phonology-syntax interface in a modular view of language. It derives the effects of (morpho)syntactic structure on prosody without referring to that structure in the phonological computation, contra the alignment constraints that map (morpho)syntactic edges to prosodic ones in Prosodic Phonology (Selkirk 1986, 1995, Truckenbrodt 1999 inter alia). It provides an explicit account of how the outputs of different phases get linearized wrt each other, providing arguments that spell-out does not proceed in chunks but produces cumulative cyclic input to phonology. It argues phonological computation needs to proceed in phases in order to achieve domain mapping while maintaining an input to phonology consisting of purely phonological information. An analysis is provided deriving prosodic domains from phases by phonological computation being faithful to the prosodification output of the previous phase, introducing Phase-Phase Faithfulness to Optimality Theory. Languages with cyclic effects at Prosodic Word level (exemplified by Kayardild and English) differ from languages with cyclic effects at Foot level (exemplified by Ojibwa) by ranking Phase-Phase faithfulness constraints differently wrt prosodic well-formedness constraints regulating e.g. binarity of prosodic constituents or their alignment to one another.